Effective shear strength parameters of remoulded residual soil - Salih, Asmaa (2012)
Lots of s oil's geotechnical characteristics involved in the construction problems. Soil will eventually reach failure and de forming excessively when it is s ubjected to gradually increasing load. This failure is related to th e shear strength which is considered as one of the most important engineering properties of the soil. This research focused on comparison of effective shear strength parameters (c', φ') that obtained from both CU and CD triaxial tests for remoulded residual soil (silt). This paper presents a reduction factor that helps to evaluate the effective internal friction angle of CD test from the results of CU test. The reduction factor is in the range of 0.89 to 0.92 that came as a resu lt of our study to samp les of residual soil with deferent initial water co ntent. The initial water co ntent had an influence in triaxial compression testing on the soil strength; soil effective cohesion became higher in the range of (11% up to 29 %) wh en initial water con tent changed from 5 3% to 43%, and soil effective friction angle would increase by (3% up to 6%).